Reproductive features of Gerres longirostris Lacepède, 1801 (Perciformes: Gerreidae) off the Red Sea coast of Jeddah, Saudi Arabia - Gabr Mohamed Hosny; Al-Harbi Mamdoh Ali; Sumon Md Afsar Ahmed (Oceanological and Hydrobiological Studies)
Sustainable management and conservation strategies are crucial for any species of Gerreidae. Without comprehensive research on population biology, maintaining a balance between having healthy natural stocks and the socio-economic benefit of fisheries is difficult. Therefore, we studied some aspects of the biology of Gerres longirostris based on 474 specimens collected from the Red Sea (Jeddah coast, Saudi Arabia). The overall sex ratio of males to females was found to be 1:1.52, which was significantly different from the expected ratio of 1:1 (p < 0.05). Histological analysis of ovaries and testes and monthly variations in GSI values for G. longirostris indicated that spawning occurs between March and June, with a peak in GSI in May, and the trend was similar for both sexes. Size at 50% sexual maturity was estimated at 19.8 cm for females and 20.2 cm for males. The maximum batch and relative fecundity were estimated at 315,210 ova, 10,832 ova/cm, and 1068 ova/g, respectively. Batch fecundity and relative batch fecundity were significant correlated with total length (TL, cm) and body weight (BW, g) at p < 0.05. Histological examination of gonads revealed that their maturation in this species is asynchronous, with different developmental stages of oocytes at the same time, which indicates that the species is a multiple-batch spawner with indeterminate fecundity.